Management Research in Private Institutions of India: Opportunities and Challenges - Srivastava, Manoj Kumar; Gupta, Om Jee (The journal of contemporary issues in business and government, 2021)
Despite, continuously emphasizing on research in management institutions and other academic institutions of higher education in India, management institution have not yet met world standards in research. There is a paradoxical situation, among all the researches in management field from India are contributed majorly by premier government institutions which are less in number, though the number of private management institutions in India is more than sufficient in numbers. In this paper an effort is made to understand the present situation of management researches in India, opportunities and challenges in private management institutions. For understanding the present status of management researches, reports of reputed agencies are studied, for assessing the opportunities in private institutions data from AICTE is taken to be analyzed, whereas for figuring out the challenges, a sample of 50 faculty members from private institutions is taken, then their views on an open ended question is analyzed.